Notes on Indian wolf spiders: I. Genus Evippa Simon, 1882 (Araneae: Lycosidae, Evippinae) - Sankaran, Pradeep M.; Caleb, John T.d.; Sebastian, Pothalil A. (Zootaxa, 2021)
Indian wolf spider species of the genus Evippa Simon, 1882 based on the type material available in the National Zoological Collection, Zoological Survey of India, Kolkata are revised. One new synonymy is recognised: Evippa mandlaensis Gajbe, 2004 syn. nov. is synonymised with Wadicosa fidelis (O. Pickard-Cambridge, 1872). All the type material examined are imaged and supplementary descriptions for Evippa shivajii Tikader & Malhotra, 1980, Evippa sohani Tikader & Malhotra, 1980, and Evippa solanensis Tikader & Malhotra, 1980 are provided.